Concrete and production method thereof

By using hydrogel composite fibers, borax, calcium stearate and other raw materials in concrete, the cracking problem of traditional concrete pavement under load and environment is solved, and high compression, cracking and freeze-thaw resistance is achieved. The performance extends the service life of concrete.

CN119461977APending Publication Date: 2025-02-18SUINING TAINING BUILDING MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411648814.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Under the influence of vehicle loads and rainy and snowy environments, traditional concrete pavement is prone to internal and surface rupture, resulting in potholes, affecting the bearing capacity and normal use.

Method used

A new concrete formula is adopted, including cement, coarse aggregate, fine aggregate, fly ash, slag powder, hydrogel composite fiber, borax, calcium stearate, polycarboxylic acid water reducer and modified emulsified asphalt. Through the synergistic effect of these raw materials, the compressive strength, crack resistance and freeze-thaw resistance of concrete are improved.

Benefits of technology

The new concrete has high compressive strength, split tensile strength, low cracking area and permeability, good durability, and can maintain a low mass loss rate in freeze-thaw resistance tests and extend the service life of the concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140361680000121
    Figure BDA0005140361680000121
  • Figure BDA0005140361680000122
    Figure BDA0005140361680000122
  • Figure BDA0005140361680000131
    Figure BDA0005140361680000131
Patent Text Reader

Abstract

The invention discloses concrete and a production method thereof. The concrete is prepared from the following raw materials in parts by weight: 100 to 120 parts of cement, 130 to 145 parts of coarse aggregate, 120 to 135 parts of fine aggregate, 10 to 25 parts of fly ash, 20 to 35 parts of slag powder, 25 to 38 parts of hydrogel composite fiber, 8 to 15 parts of borax, 6 to 11 parts of calcium stearate, 2 to 3 parts of polycarboxylate superplasticizer, 30 to 40 parts of modified emulsified asphalt and 50 to 65 parts of water. Wherein the hydrogel composite fiber is prepared from expanded perlite micro powder, polyurethane, polyacrylic acid and a hydrogel polymer through spinning. The concrete provided by the invention has good permeability resistance, compressive strength and toughness, and also has good freeze thawing resistance; the production method is simple, easy to operate and convenient to construct.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to concrete and a production method thereof, belonging to the technical field of concrete. Background Art

[0002] Concrete is a general term for engineering composite materials that are made of aggregates bonded together by cementitious materials. It has the characteristics of high compressive strength, good durability, and a wide range of strength grades, which makes the use of concrete more extensive. For example, cement concrete, as one of the main materials for road construction and repair, is widely used in municipal roads, highways, national and provincial trunk roads, etc. However, under the influence of vehicle loads and rain and snow environmental factors, after a period of use, the interior and surface of the traditional concrete pavement will crack and have potholes, which will not only affect people's travel, but also affect the bearing capacity and normal use of the concrete pavement. For this reason, the present invention provides a concrete and a production method thereof. Summary of the invention

[0003] In order to solve at least one problem existing in the above-mentioned prior art, the present invention provides a concrete and a production method thereof, wherein the concrete has good anti-permeability, compressive strength and toughness, and also has good anti-freezing and thawing properties; and the production method thereof is simple and easy to operate, and is convenient for construction.

[0004] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a concrete, comprising the following raw materials and their weight proportions: 100-120 parts of cement, 130-145 parts of coarse aggregate, 120-135 parts of fine aggregate, 10-25 parts of fly ash, 20-35 parts of slag powder, 25-38 parts of hydrogel composite fiber, 8-15 parts of borax, 6-11 parts of calcium stearate, 2-3 parts of polycarboxylic acid water reducer, 30-40 parts of modified emulsified asphalt and 50-65 parts of water; wherein the hydrogel composite fiber is prepared by spinning expanded perlite powder, polyurethane, polyacrylic acid and hydrogel polymer.

[0005] Preferably, the concrete includes the following raw materials and their weight parts: 112 parts of cement, 137 parts of coarse aggregate, 130 parts of fine aggregate, 19 parts of fly ash, 31 parts of slag powder, 33 parts of hydrogel composite fiber, 12 parts of borax, 9 parts of calcium stearate, 2.5 parts of polycarboxylate water reducer, 36 parts of modified emulsified asphalt and 58 parts of water.

[0006] Preferably, the sum of the mass of the fly ash and the slag powder accounts for 30-55% of the mass of the cement.

[0007] Preferably, the coarse aggregate is fine stone, and the particle size of the fine stone is 5 to 10 mm.

[0008] Preferably, the fine aggregate includes coarse sand and fine sand in a mass ratio of 3-3.5:1.5; the fineness modulus of the coarse sand is 3.35-3.5; and the fineness modulus of the fine sand is 1.95-2.15.

[0009] Preferably, the modified emulsified asphalt is one of SBR modified emulsified asphalt or CR type emulsified asphalt.

[0010] Preferably, the modified emulsified asphalt is SBR modified emulsified asphalt.

[0011] Preferably, the method for preparing the hydrogel composite fiber is as follows: expanded perlite powder, polyurethane, polyacrylic acid and hydrogel polymer are mixed evenly, added to a mixed solvent consisting of dimethylacetamide and water in a volume ratio of 1.5:1 to form a hydrogel mixture, and the mixture is spun into filamentous fibers by extrusion or drawing, and then freeze-dried to obtain hydrogel composite fibers.

[0012] Preferably, in the hydrogel mixture, the content of expanded perlite powder is 2-3wt%, the content of polyurethane is 6-8wt%, the content of polyacrylic acid is 5-7wt%, and the content of hydrogel polymer is 5-8wt%.

[0013] Preferably, in the hydrogel mixture, the content of the expanded perlite powder is 2.6wt%, the content of the polyurethane is 6.5wt%, the content of the polyacrylic acid is 6wt%, and the content of the hydrogel polymer is 6.8wt%.

[0014] Preferably, the hydrogel polymer comprises one or more of polyvinyl alcohol, chitosan or sodium alginate.

[0015] Preferably, the hydrogel polymer comprises polyvinyl alcohol and sodium alginate.

[0016] Preferably, the hydrogel polymer comprises polyvinyl alcohol and sodium alginate mixed in a mass ratio of 5 to 6:4.

[0017] The present invention also provides a method for producing concrete, the specific steps of which are as follows:

[0018] (1) Preparation of hydrogel composite fiber: After the expanded pearlite powder, polyurethane, polyacrylic acid and hydrogel polymer are mixed evenly, they are added to a mixed solvent composed of dimethylacetamide and water in a volume ratio of 1.5:1 to form a hydrogel mixed solution, in which the content of the expanded pearlite powder is 2-3%, the content of the polyurethane is 6-8wt%, the content of the polyacrylic acid is 5-7%, and the content of the hydrogel polymer is 5-8wt%. After being spun into filamentous fibers by extrusion or drawing, the fibers are freeze-dried to obtain hydrogel composite fibers for later use;

[0019] (2) uniformly mixing the above-mentioned parts by weight of borax, calcium stearate, polycarboxylate water reducer and water to form a mixture A;

[0020] (3) Mixing the above-mentioned parts by weight of cement, coarse aggregate, fine aggregate, fly ash, slag powder and hydrogel composite fiber uniformly to form a mixture B;

[0021] (4) Adding mixture A to mixture B and stirring to mix evenly, then adding modified emulsified asphalt and stirring to mix evenly to form concrete slurry, pouring and curing the concrete slurry to obtain concrete.

[0022] The beneficial effects of the present invention are as follows: in the concrete of the present invention, by adding borax, calcium stearate, hydrogel composite fiber, slag powder, fly ash and modified emulsified asphalt to cooperate with each other, the concrete has higher compressive strength and splitting tensile strength, lower cracking area and penetration height, and good durability; the concrete of the present invention has lower compressive strength and mass loss rate after freeze-thaw resistance test, and the durability of the concrete is further improved; the hydrogel composite fiber used in the present invention is prepared by expanded perlite powder, polyurethane, polyacrylic acid and hydrogel polymer, which can effectively improve the synergistic effect of the hydrogel composite fiber and concrete, better improve the microstructure of the concrete, and further improve the mechanical properties, freeze-thaw resistance and impermeability of the concrete. DETAILED DESCRIPTION

[0023] The following is a clear and complete description of the technical solutions in the implementation of the present invention. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents, instruments, and components used, they are all conventional products that can be purchased commercially.

[0024] Example 1

[0025] A concrete comprises the following raw materials and their weight parts: 100 parts of cement, 130 parts of coarse aggregate, 120 parts of fine aggregate, 10 parts of fly ash, 20 parts of slag powder, 25 parts of hydrogel composite fiber, 8 parts of borax, 6 parts of calcium stearate, 2 parts of polycarboxylate water reducer, 30 parts of SBR modified emulsified asphalt and 50 parts of water; wherein the coarse aggregate is fine stone with a particle size of 5 to 10 mm; the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3:1.5; the fineness modulus of the coarse sand is 3.35 to 3.5; the fineness modulus of the fine sand is 1.95 to 2.15;

[0026] The specific production steps are as follows:

[0027] (1) Preparation of hydrogel composite fiber: After the expanded pearlite powder, polyurethane, polyacrylic acid and hydrogel polymer are mixed evenly, they are added to a mixed solvent composed of dimethylacetamide and water in a volume ratio of 1.5:1 to form a hydrogel mixed solution, in which the expanded pearlite powder content is 2wt%, the polyurethane content is 6wt%, the polyacrylic acid content is 5wt%, and the hydrogel polymer content is 5wt%, and then the hydrogel composite fiber is obtained by extrusion spinning into filamentous fibers, and then freeze-drying, and the hydrogel composite fiber is used for standby use; wherein the hydrogel polymer is polyvinyl alcohol;

[0028] (2) uniformly mixing the above-mentioned parts by weight of borax, calcium stearate, polycarboxylate water-reducing agent and water to form a mixture A;

[0029] (3) Mixing the above-mentioned parts by weight of cement, coarse aggregate, fine aggregate, fly ash, slag powder and hydrogel composite fiber uniformly to form a mixture B;

[0030] (4) Adding mixture A to mixture B and stirring to mix evenly, then adding SBR modified emulsified asphalt and stirring to mix evenly to form concrete slurry, pouring and curing the concrete slurry to obtain concrete.

[0031] Example 2

[0032] A concrete comprises the following raw materials and their weight parts: 110 parts of cement, 135 parts of coarse aggregate, 125 parts of fine aggregate, 12 parts of fly ash, 26 parts of slag powder, 30 parts of hydrogel composite fiber, 10 parts of borax, 8 parts of calcium stearate, 2.3 parts of polycarboxylate water reducer, 33 parts of SBR modified emulsified asphalt and 55 parts of water; wherein the coarse aggregate is fine stone with a particle size of 5 to 10 mm; the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3:1.5; the fineness modulus of the coarse sand is 3.35 to 3.5; the fineness modulus of the fine sand is 1.95 to 2.15;

[0033] Its production steps are exactly the same as those in Example 1.

[0034] Example 3

[0035] A concrete comprises the following raw materials and their weight parts: 112 parts of cement, 137 parts of coarse aggregate, 130 parts of fine aggregate, 19 parts of fly ash, 31 parts of slag powder, 33 parts of hydrogel composite fiber, 12 parts of borax, 9 parts of calcium stearate, 2.5 parts of polycarboxylate water reducer, 36 parts of SBR modified emulsified asphalt and 58 parts of water; wherein the coarse aggregate is fine stone with a particle size of 5 to 10 mm; the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3:1.5; the fineness modulus of the coarse sand is 3.35 to 3.5; the fineness modulus of the fine sand is 1.95 to 2.15;

[0036] Its production steps are exactly the same as those in Example 1.

[0037] Example 4

[0038] A concrete comprises the following raw materials and their weight parts: 120 parts of cement, 145 parts of coarse aggregate, 135 parts of fine aggregate, 25 parts of fly ash, 35 parts of slag powder, 38 parts of hydrogel composite fiber, 15 parts of borax, 11 parts of calcium stearate, 3 parts of polycarboxylate water reducer, 40 parts of SBR modified emulsified asphalt and 65 parts of water; wherein the coarse aggregate is fine stone with a particle size of 5 to 10 mm; the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3:1.5; the fineness modulus of the coarse sand is 3.35 to 3.5; the fineness modulus of the fine sand is 1.95 to 2.15;

[0039] Its production steps are exactly the same as those in Example 1.

[0040] Example 5

[0041] A concrete comprises the following raw materials and their weight parts: 110 parts of cement, 145 parts of coarse aggregate, 135 parts of fine aggregate, 25 parts of fly ash, 35 parts of slag powder, 38 parts of hydrogel composite fiber, 15 parts of borax, 11 parts of calcium stearate, 3 parts of polycarboxylate water reducer, 40 parts of SBR modified emulsified asphalt and 65 parts of water; wherein the coarse aggregate is fine stone with a particle size of 5 to 10 mm; the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3:1.5; the fineness modulus of the coarse sand is 3.35 to 3.5; the fineness modulus of the fine sand is 1.95 to 2.15;

[0042] Its production steps are exactly the same as those in Example 1.

[0043] Example 6

[0044] A concrete comprises the following raw materials and their weight parts: 100 parts of cement, 145 parts of coarse aggregate, 135 parts of fine aggregate, 25 parts of fly ash, 33 parts of slag powder, 38 parts of hydrogel composite fiber, 15 parts of borax, 11 parts of calcium stearate, 3 parts of polycarboxylate water reducer, 40 parts of SBR modified emulsified asphalt and 65 parts of water; wherein the coarse aggregate is fine stone with a particle size of 5 to 10 mm; the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3:1.5; the fineness modulus of the coarse sand is 3.35 to 3.5; the fineness modulus of the fine sand is 1.95 to 2.15;

[0045] Its production steps are exactly the same as those in Example 1.

[0046] Example 7

[0047] A concrete comprises the following raw materials and their weight parts: 120 parts of cement, 145 parts of coarse aggregate, 135 parts of fine aggregate, 11 parts of fly ash, 21 parts of slag powder, 38 parts of hydrogel composite fiber, 15 parts of borax, 11 parts of calcium stearate, 3 parts of polycarboxylate water reducer, 40 parts of SBR modified emulsified asphalt and 65 parts of water; wherein the coarse aggregate is fine stone with a particle size of 5 to 10 mm; the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3:1.5; the fineness modulus of the coarse sand is 3.35 to 3.5; the fineness modulus of the fine sand is 1.95 to 2.15;

[0048] Its production steps are exactly the same as those in Example 1.

[0049] Example 8

[0050] A concrete, wherein the raw materials and weight proportions thereof are the same as those in Example 3, and the production steps are partially the same as those in Example 1, except that: in step (1), in the hydrogel mixed solution, the content of the expanded perlite powder is 2.6wt%, the content of the polyurethane is 6.5wt%, the content of the polyacrylic acid is 6wt%, and the content of the hydrogel polymer is 6.8wt%.

[0051] Example 9

[0052] A concrete, wherein the raw materials and weight proportions thereof are the same as those in Example 3, and the production steps are partially the same as those in Example 1, except that: in step (1), in the hydrogel mixed solution, the content of the expanded perlite powder is 3wt%, the content of the polyurethane is 8wt%, the content of the polyacrylic acid is 7wt%, and the content of the hydrogel polymer is 8wt%.

[0053] Example 10

[0054] A concrete, wherein the raw materials and weight proportions thereof are the same as those in Example 3, and the production steps are partially the same as those in Example 1, except that: in step (1), in the hydrogel mixed solution, the content of the expanded perlite powder is 2wt%, the content of the polyurethane is 6.1wt%, the content of the polyacrylic acid is 5.3wt%, and the content of the hydrogel polymer is 7.5wt%.

[0055] Embodiment 11

[0056] A concrete, wherein the raw materials and weight proportions thereof are the same as those in Example 3, and the production steps are partially the same as those in Example 1, except that: in step (1), in the hydrogel mixed solution, the content of the expanded perlite powder is 2.7wt%, the content of the polyurethane is 8wt%, the content of the polyacrylic acid is 6.8wt%, and the content of the hydrogel polymer is 5.2wt%.

[0057] Example 12

[0058] A concrete, the raw materials and weight parts thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is chitosan;

[0059] The production steps are completed according to the production steps of Example 8, and chitosan is used instead of polyvinyl alcohol.

[0060] Embodiment 13

[0061] A concrete, the raw materials and weight parts thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is sodium alginate;

[0062] The production steps are completed according to the production steps of Example 8, and sodium alginate is used instead of polyvinyl alcohol.

[0063] Embodiment 14

[0064] A concrete, the raw materials and weight proportions thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is polyvinyl alcohol, chitosan and sodium alginate mixed in a mass ratio of 1:1:1;

[0065] The production steps are completed according to the production steps of Example 8, and polyvinyl alcohol, chitosan and sodium alginate are mixed in a mass ratio of 1:1:1 to replace polyvinyl alcohol.

[0066] Embodiment 15

[0067] A concrete, the raw materials and weight parts thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is polyvinyl alcohol and chitosan mixed in a mass ratio of 1:1;

[0068] The production steps were completed according to the production steps of Example 8, and polyvinyl alcohol and chitosan were mixed in a mass ratio of 1:1 to replace polyvinyl alcohol.

[0069] Example 16

[0070] A concrete, the raw materials and weight parts thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is chitosan and sodium alginate mixed in a mass ratio of 1:1;

[0071] The production steps were completed according to the production steps of Example 8, and chitosan and sodium alginate were mixed in a mass ratio of 1:1 to replace polyvinyl alcohol.

[0072] Embodiment 17

[0073] A concrete, the raw materials and weight parts thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is polyvinyl alcohol and sodium alginate mixed in a mass ratio of 1:1;

[0074] The production steps were completed according to the production steps of Example 8, and polyvinyl alcohol and sodium alginate were mixed in a mass ratio of 1:1 to replace polyvinyl alcohol.

[0075] Embodiment 18

[0076] A concrete, the raw materials and weight parts thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is polyvinyl alcohol and sodium alginate mixed in a mass ratio of 5:4;

[0077] The production steps were completed according to the production steps of Example 8, and polyvinyl alcohol and sodium alginate were mixed in a mass ratio of 5:4 to replace polyvinyl alcohol.

[0078] Embodiment 19

[0079] A concrete, the raw materials and weight parts thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is polyvinyl alcohol and sodium alginate mixed in a mass ratio of 6:4;

[0080] The production steps were completed according to the production steps of Example 8, and polyvinyl alcohol and sodium alginate were mixed in a mass ratio of 6:4 to replace polyvinyl alcohol.

[0081] Embodiment 20

[0082] A concrete, the raw materials and weight proportions thereof are the same as those in Example 8, except that: the hydrogel polymer in the hydrogel composite fiber is polyvinyl alcohol and sodium alginate mixed in a mass ratio of 7:4;

[0083] The production steps were completed according to the production steps of Example 8, and polyvinyl alcohol and sodium alginate were mixed in a mass ratio of 7:4 to replace polyvinyl alcohol.

[0084] Embodiment 21

[0085] A concrete, wherein the raw materials and weight portions thereof are partially the same as those in Example 19, except that: the modified emulsified asphalt is CR type emulsified asphalt;

[0086] Its production steps are exactly the same as those in Example 19.

[0087] Embodiment 22

[0088] A concrete, wherein the raw materials and weight portions thereof are partially the same as those of Example 19, except that: the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3.5:1.5; the fineness modulus of the coarse sand is 3.35-3.5; the fineness modulus of the fine sand is 1.95-2.15;

[0089] Its production steps are exactly the same as those in Example 19.

[0090] Embodiment 23

[0091] A concrete, wherein the raw materials and weight portions thereof are partially the same as those of Example 19, except that: the fine aggregate comprises coarse sand and fine sand in a mass ratio of 3.25:1.5; the fineness modulus of the coarse sand is 3.35-3.5; the fineness modulus of the fine sand is 1.95-2.15;

[0092] Its production steps are exactly the same as those in Example 19.

[0093] Embodiment 24

[0094] A concrete, the raw materials and weight parts thereof are the same as those in Example 5, except that: the hydrogel polymer in the hydrogel composite fiber is polyvinyl alcohol and sodium alginate mixed in a mass ratio of 6:4;

[0095] The production steps were completed according to the production steps of Example 5, and polyvinyl alcohol and sodium alginate were mixed in a mass ratio of 6:4 to replace polyvinyl alcohol.

[0096] Comparative Example 1

[0097] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: no borax is contained;

[0098] The production steps are completed according to Example 1 without adding borax.

[0099] Comparative Example 2

[0100] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: calcium stearate is not contained;

[0101] The production steps are completed according to Example 1, and calcium stearate is not added.

[0102] Comparative Example 3

[0103] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: it does not contain hydrogel composite fibers;

[0104] The production steps are completed according to Example 1, and no hydrogel composite fiber is added.

[0105] Comparative Example 4

[0106] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: modified emulsified asphalt is not contained, and water is 70 parts;

[0107] The production steps are completed according to Example 1, and no modified emulsified asphalt is added.

[0108] Comparative Example 5

[0109] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: fly ash is not contained and slag powder is 30 parts;

[0110] The production steps are completed according to Example 1, and no fly ash is added.

[0111] Comparative Example 6

[0112] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: slag powder is not contained, and fly ash is 30 parts;

[0113] The production steps are completed according to Example 1, and no slag powder is added.

[0114] Comparative Example 7

[0115] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: the hydrogel composite fiber does not contain expanded perlite powder;

[0116] The production steps are completed according to Example 1, and in the hydrogel mixture, the content of expanded pearlite powder is 0wt%, the content of polyurethane is 6wt%, the content of polyacrylic acid is 5wt%, and the content of hydrogel polymer is 5wt%.

[0117] Comparative Example 8

[0118] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: the hydrogel composite fiber does not contain polyurethane;

[0119] The production steps are completed according to Example 1, and in the hydrogel mixture, the content of expanded pearlite powder is 2wt%, the content of polyurethane is 0wt%, the content of polyacrylic acid is 5wt%, and the content of hydrogel polymer is 5wt%.

[0120] Comparative Example 9

[0121] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: the hydrogel composite fiber does not contain polyacrylic acid;

[0122] The production steps are completed according to Example 1, and in the hydrogel mixture, the content of expanded pearlite powder is 2wt%, the content of polyurethane is 6wt%, the content of polyacrylic acid is 0wt%, and the content of hydrogel polymer is 5wt%.

[0123] Comparative Example 10

[0124] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: the hydrogel composite fiber does not contain a hydrogel polymer;

[0125] The production steps are completed according to Example 1, and in the hydrogel mixture, the content of expanded pearlite powder is 2wt%, the content of polyurethane is 6wt%, the content of polyacrylic acid is 5wt%, and the content of hydrogel polymer is 0wt%.

[0126] Comparative Example 11

[0127] A concrete, the raw materials and their weight parts are the same as those in Example 1, except that: only polyurethane and hydrogel polymer are used in the preparation of the hydrogel composite fiber;

[0128] The production steps are completed according to Example 1, and in the hydrogel mixture, the content of expanded pearlite powder is 0wt%, the content of polyurethane is 6wt%, the content of polyacrylic acid is 0wt%, and the content of hydrogel polymer is 5wt%.

[0129] Comparative Example 12

[0130] A concrete, the raw materials and weight parts thereof are the same as those in Example 1, except that: only polyacrylic acid and hydrogel polymer are used in the preparation of the hydrogel composite fiber;

[0131] The production steps are completed according to Example 1, and in the hydrogel mixture, the content of expanded pearlite powder is 0wt%, the content of polyurethane is 0wt%, the content of polyacrylic acid is 5wt%, and the content of hydrogel polymer is 5wt%.

[0132] The concrete prepared in Examples 1 to 24 and Comparative Examples 1 to 12 were subjected to performance tests.

[0133] The compressive strength and splitting tensile strength after curing for 28 days were measured according to GB / T50081-2019 "Standard for Test Methods of Physical Properties of Concrete". The water seepage height was tested according to GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", where the water seepage height was tested by the step-by-step pressurization method, and the test results are shown in Tables 1 and 2.

[0134] Table 1

[0135]

[0136] Table 2

[0137]

[0138]

[0139] As can be seen from Table 1 and Table 2, compared with Example 1, Comparative Examples 1 to 6 show that when borax, calcium stearate, hydrogel composite fiber, slag powder, fly ash and modified emulsified asphalt are added to the concrete, the compressive strength and splitting tensile strength of the prepared concrete are significantly improved, the cracking area and penetration height of the concrete are uniformly and significantly reduced, and the compressive strength and mass loss rate of the concrete in the freeze-thaw resistance test are both reduced. This is mainly because calcium stearate and borax increase the cohesion and surface tension of the concrete, while borax, calcium stearate and hydrogel composite fibers are combined to optimize the microstructure of the concrete, thereby improving the strength, crack resistance, permeability and freeze-thaw resistance of the concrete; in addition, fly ash and cement produce a product with gel properties, and the complementary advantages of slag powder and fly ash are formed to reduce the thermal expansion and contraction of the concrete, so that the density of the concrete is more stable, which is helpful for shrinkage cracks and further improves the durability of the concrete; and by adding modified emulsified asphalt, the bonding force between the components in the concrete is increased, and the permeability and freeze-thaw resistance of the concrete are effectively improved.

[0140] Comparative Examples 1 to 6 show that compared with Example 1, the raw materials for preparing the hydrogel composite fiber have a certain influence on the performance of the concrete. The hydrogel composite fiber prepared by the composition of expanded perlite powder, polyurethane, polyacrylic acid and hydrogel polymer can effectively improve the synergistic effect of the hydrogel composite fiber and concrete, and better improve the microstructure of the concrete. The polyurethane and polyacrylic acid synergistically form complementary advantages, so that the hydrogel composite fiber and cement form a good crystal structure and fine crystals, reduce the defects inside the concrete, and improve the internal density and cohesion of the concrete; at the same time, the hydrogel polymer cooperates with polyurethane and polyacrylic acid to form a bond between the hydrogel composite fiber and the cement, so that the concrete maintains an appropriate humidity during hardening, and improves the quality of the concrete; in addition, the expanded perlite powder improves the pore structure of the hydrogel composite fiber through its own pore structure, so that the hydrogel composite fiber can improve the thermal insulation performance of the concrete, further improve the freeze-thaw resistance of the concrete, and reduce the mechanical properties and mass loss rate of the concrete.

[0141] In summary, the concrete used in the present invention has good anti-permeability, compressive strength and toughness, and also has good freeze-thaw resistance; the production method is simple and easy to operate, and is convenient for construction.

[0142] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0143] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A concrete, characterized in that: The invention comprises the following raw materials and their weight parts: 100-120 parts of cement, 130-145 parts of coarse aggregate, 120-135 parts of fine aggregate, 10-25 parts of fly ash, 20-35 parts of slag powder, 25-38 parts of hydrogel composite fiber, 8-15 parts of borax, 6-11 parts of calcium stearate, 2-3 parts of polycarboxylate water reducer, 30-40 parts of modified emulsified asphalt and 50-65 parts of water; The hydrogel composite fiber is prepared by spinning expanded perlite powder, polyurethane, polyacrylic acid and hydrogel polymer.

2. A concrete according to claim 1, characterized in that: The total mass of the fly ash and slag powder accounts for 30-55% of the mass of the cement.

3. A concrete according to claim 1, characterized in that: The concrete includes the following raw materials and their weight parts: 112 parts of cement, 137 parts of coarse aggregate, 130 parts of fine aggregate, 19 parts of fly ash, 31 parts of slag powder, 33 parts of hydrogel composite fiber, 12 parts of borax, 9 parts of calcium stearate, 2.5 parts of polycarboxylate water reducer, 36 parts of modified emulsified asphalt and 58 parts of water.

4. A concrete according to claim 1, characterized in that: The preparation method of the hydrogel composite fiber comprises the following steps: uniformly mixing expanded perlite powder, polyurethane, polyacrylic acid and a hydrogel polymer, adding the mixture to a mixed solvent consisting of dimethylacetamide and water in a volume ratio of 1.5:1 to form a hydrogel mixed solution, spinning the mixed solution into filamentous fibers by extrusion or drawing, and freeze-drying the mixed solution to obtain the hydrogel composite fiber.

5. A concrete according to claim 4, characterized in that: In the hydrogel mixed solution, the content of the expanded pearlite powder is 2-3wt%, the content of the polyurethane is 6-8wt%, the content of the polyacrylic acid is 5-7wt%, and the content of the hydrogel polymer is 5-8wt%.

6. A concrete according to claim 5, characterized in that: In the hydrogel mixed solution, the content of the expanded pearlite powder is 2.6wt%, the content of the polyurethane is 6.5wt%, the content of the polyacrylic acid is 6wt%, and the content of the hydrogel polymer is 6.8wt%.

7. The concrete according to any one of claims 1 to 6, characterized in that: The hydrogel polymer includes one or more of polyvinyl alcohol, chitosan or sodium alginate.

8. The concrete according to claim 7, characterized in that: The hydrogel polymer includes polyvinyl alcohol and sodium alginate.

9. The concrete according to claim 1, characterized in that: Modified emulsified asphalt is a type of SBR modified emulsified asphalt or CR type emulsified asphalt.

10. A method for producing concrete according to claim 1, characterized in that: The production method steps are as follows: (1) Preparation of hydrogel composite fiber: After the expanded pearlite powder, polyurethane, polyacrylic acid and hydrogel polymer are mixed evenly, they are added to a mixed solvent composed of dimethylacetamide and water in a volume ratio of 1.5:1 to form a hydrogel mixed solution, in which the content of the expanded pearlite powder is 2-3%, the content of the polyurethane is 6-8wt%, the content of the polyacrylic acid is 5-7%, and the content of the hydrogel polymer is 5-8wt%. After being spun into filamentous fibers by extrusion or drawing, the fibers are freeze-dried to obtain hydrogel composite fibers for later use; (2) uniformly mixing the above-mentioned parts by weight of borax, calcium stearate, polycarboxylate water-reducing agent and water to form a mixture A; (3) Mixing the above-mentioned parts by weight of cement, coarse aggregate, fine aggregate, fly ash, slag powder and hydrogel composite fiber uniformly to form a mixture B; (4) Adding mixture A to mixture B and stirring to mix evenly, then adding modified emulsified asphalt and stirring to mix evenly to form concrete slurry, pouring and curing the concrete slurry to obtain concrete.

Citation Information

Cited By

  • High-performance material for concrete foundation reinforcement and preparation method thereof

    CN122520389A